2008
DOI: 10.1002/kin.20338
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic and mechanistic investigation into the influence of chelate substituents on the substitution reactions of platinum(II) terpyridine complexes

Abstract: The substitution kinetics of the complexes [Pt{4 -(o -CH 3 -Ph)-terpy} Cl]SbF 6 (CH 3 PhPtCl(Sb)), (ClPhPtCl), and [Pt{4 -(o -CF 3 -Ph)-terpy}Cl]SbF 6 (CF 3 PhPtCl), where terpy is 2,2 :6 ,2 -terpyridine, with the nucleophiles thiourea (TU), N,N -dimethylthiourea (DMTU), and N,N,N ,Ntetramethylthiourea (TMTU) were investigated in methanol as a solvent. The substitution reactions of the chloride displacement from the metal complexes by the nucleophiles were investigated as a function of nucleophile concentrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 59 publications
2
9
0
Order By: Relevance
“…Thus, it can be concluded that the differences in the rate of substitution of all the complexes investigated are purely electronic in origin. This is similar to what has been reported in the literature [47].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Thus, it can be concluded that the differences in the rate of substitution of all the complexes investigated are purely electronic in origin. This is similar to what has been reported in the literature [47].…”
Section: Discussionsupporting
confidence: 92%
“…It is known that changing its electronic properties influences the Scheme 2 Proposed mechanism of chloride substitution from the investigated complexes by a series of azole nucleophiles [48,49] and r-effects [34,47,50] have been shown to influence the reactivity depending on the moiety attached to the ancillary position on the terpy or on modification of the ligand attachment in the cis position of the metal centre. In the case of p-back-bonding, the terpy ligand accepts electron density from the platinum metal d-orbitals into its vacant p-orbitals rendering the metal centre more electrophilic.…”
Section: Discussionmentioning
confidence: 99%
“…This topic fitted in well with the coordination Chemistry studies under Field, and progress was rapid. Typical of his current research is a paper dealing with the kinetics and mechanism of platinum (II) terpyridine complexes (Jaganyi et al, 2008). The research has made great strides and the Research Group is now a very viable one, with input from local students as well as others from Kenya and Tanzania.…”
Section: The Era Of John Stainer Field 1996-2004mentioning
confidence: 99%
“…Platinum(II) chelates have been extensively studied since their application as antitumour agents was discovered in the 1960s (Jaganyi et al, 2008). Although cis-diamminedichloroplatinum(II) (cisplatin) has been effective in the treatment of particular tumour cell lines, cisplatin resistance in certain cancer cell lines has sparked much research into developing new-generation platinum-based drugs (Thurston, 2007).…”
Section: Commentmentioning
confidence: 99%
“…The substitution kinetics of the title metal chelate have been studied to further develop the understanding of the interactions between the Pt II ion and various nucleophiles. This research is critical to the development of new drugs (Jaganyi et al, 2008). The structure of the title pyrazole-substituted terpyridine-platinum(II) compound, [Pt(pyz)(terpy)](ClO 4 ) 2 Á-CH 3 NO 2 (where terpy is 2,2 0 :6 0 ,2 00 -terpyridine and pyz is pyrazole), (I), was elucidated to further develop the under-standing of the binding mode of the ancillary ligand, i.e.…”
Section: Commentmentioning
confidence: 99%